Two-Dimensional Modeling of Thermomechanical Responses of Rectangular GFRP Profiles Exposed to Fire - Lingfeng Zhang; Weiqing Liu; Guoqing Sun; Lu Wang; Lingzhi Li (Advances in Materials Science and Engineering)
In the past three decades, one-dimensional (1D) thermal model was usually used to estimate the thermal responses of glass fiber-reinforced polymer (GFRP) materials and structures. However, the temperature gradient and mechanical degradation of whole cross sections cannot be accurately evaluated. To address this issue, a two-dimensional (2D) thermomechanical model was developed to predict the thermal and mechanical responses of rectangular GFRP tubes subjected to one-side ISO-834 fire exposure in this paper. The 2D governing heat transfer equations with thermal boundary conditions, discretized by alternating direction implicit (ADI) method, were solved by Gauss-Seidel iterative approach. Then the temperature-dependent mechanical responses were obtained by considering the elastic modulus degradation from glass transition and decomposition of resin. The temperatures and midspan deflections of available experimental results can be reasonably predicted. The overestimation of deflections could be attributed to the underestimation of bending stiffness. This model can also be extended to simulate the thermomechanical responses of beams and columns subjected to multiside fire loading, which may occur in real fire scenarios.